Links between Irrigation, Agriculture, Level of Living and Poverty Scenario in West Bengal - Souvik Ghosh , D. K. Panda , A. K. Nayak , P. Nanda; H. C. Verma (Indian Journal of Extension Education, 2015)
An analysis of irrigation, agriculture, level of living and poverty linkages in eighteen districts of West Bengal was carried out. District-wise scenario of irrigation, agriculture, livelihood and poverty revealed with the help of different indices developed for the study. The values of Groundwater Development Index and Composite Irrigation Index were found low to very low for eight districts. Six districts showed high agricultural development while seven and five districts showed medium and low Agricultural Development Index values, respectively. Level of living of eleven and six districts was found medium and low, respectively. Poverty Ratio Index values of nine districts showed very high to high poverty level. The links and/or missing links between irrigation resources, agriculture development, poverty and level of living were explored.